1983
DOI: 10.1007/bf01009395
|View full text |Cite
|
Sign up to set email alerts
|

Power broadening and nonlinear FIR magneto-photoconductivity in n-GaAs

Abstract: The saturation of the photoconductivity due to Is-2p+ shallow donor transitions in n-GaAs has been investigated using a high power cw-FIR-laser. Magnetic field strengths were chosen in such a way that 2p+ energy levels were either below or above the N = O conduction band Landau level. In the former case Is-2p+ transitions are found to be inhomogeneously broadened with a saturation intensity as low as 0.84 mW/cm 2, giving an effective lifetime of the 2p+ state of 1.5 ~s. Above the band edge the integrated photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The observed effects could be attributed to impact ionization of the optically excited 2p+ state in addition to thermal ionization. Our analysis clarifies already previously observed discrepancies between the intensity dependence of the photosignal and that of linewidth which have not yet been explained [5].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The observed effects could be attributed to impact ionization of the optically excited 2p+ state in addition to thermal ionization. Our analysis clarifies already previously observed discrepancies between the intensity dependence of the photosignal and that of linewidth which have not yet been explained [5].…”
Section: Resultssupporting
confidence: 77%
“…at) -1 is the saturation photon flux density and Is the corresponding saturation intensity [9]. This approach has been used previously to evaluate the saturation of photoconductivity [5] and it is also the basis of interpretation of absorption measurements [4,6]. Assuming the mobility to be independent of n, the dependence on F of the inverse normalized photoconductivity S is given by:…”
Section: -F F/fsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free carrier concentration p, and thus the photoconductive signal AV/V, depends linearly on F for F << Fs and assumes a constant, saturated value, psat = N~i *r--~---in the high intensity limit. This approximation has been 2r~jl used to evaluate resonant impurity photoconductivity in n-GaAs at 4.2 K [3] and was also the basis of interpretation of high power absorption measurements [1,2]. It has been previously shown that at temperatures well below 4.2 K in n-GaAs excited state impact ionization dominates the optically induced free carrier generation.…”
Section: -Imentioning
confidence: 99%
“…Very detailed measurements have been performed on shallow donor transitions of n-GaAs epitaxial layers in an external magnetic field at low temperatures. As a function of the laser intensity incident on the sample, the absorption coefficient [1,2] and the photoconductive signal due to optical transitions to excited impurity states and cyclotron resonance [3,4,5] have been measured for various magnetic field strengths. The experimental results were analyzed in terms of appropriate rate equation models based on the photothermal free carrier generation process [6].…”
Section: Introductionmentioning
confidence: 99%